The Role of Artificial Intelligence in the Digital Transformation of Commercial Banks: Enhancing Efficiency, Customer Experience, and Risk Management - Tian Xuanning (SHS Web of Conferences)
In the quickly evolving financial world of today, the digital transformation of commercial banks has become critical, with artificial intelligence (AI) playing a central role in this process. This study aims to explore whether AI can significantly enhance the digital transformation of commercial banks, how it works in key business areas, and what challenges it poses. The study begins with an analysis of the core components of digital transformation, including customer-centric strategies, IT infrastructure modernization, talent and culture transformation, and data security. It then investigates how AI can strengthen these areas by improving customer loyalty, operational efficiency, and risk management, while recognizing obstacles like data security, moral dilemmas, and legal requirements. The findings show that AI significantly improves operational efficiency and customer experience, but poses ethical and compliance challenges, which need to be explored carefully. The study concluded that AI is critical in shaping the future of commercial banking, provided banks respond responsibly to its challenges. This report emphasizes AI’s capacity for transformation. and its importance in ensuring the sustainable growth and competitiveness of commercial banks.